Claster model of N2 – Ar, CO – Ar cryo alloys, comparative analysis - Mysko, N.S.; Danchuk, V.V.; Solodovnik, A.A. (Recent Contributions to Physics, 2015)
Сryocrystall solutions formed of linear molecules with atomic components are of considerable interest as convenient model systems. It is known that in some cases Vegard’s rule and Prigogine theory are insufficient and in this connection novel approaches are needed. One of the deviations from an ideal solution manifests itself through the anomalous behavior of the lattice parameter as a function of the composition. For explanation of the unusual concentration dependence of the lattice parameter in CO2 – Ar alloys the cluster model was used.